Landscape Design of Mutiara Garden Housing Park as a Source of Infiltration in Residential Areas - Morian Saspriatnadi; Gun Faisal; Indra Kuswoyo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Green Open Space (RTH) plays an important role in the ecosystem and balance for both living things and the surrounding environment. The condition of the planning site that extends north to south is in the middle of a housing complex. The planned facilities include a playground, watersplash plaza, children's pool, seating corner, gazebo, community garden, tropical pocket park and tropical striping park, veranda walkway. With the concept of